Anti-Doping Monitoring Web-Based Android for Athletes Disabilities - Fadilah Umar; Dina Listiani; Slamet Riyadi; Misbah Misbah (CV. FOUNDAE, 2024)
The usage of doping has been banned in the world of sports. This ban is regulated by law and must be adhered to by all athletes. This research aimed to identify the need for efforts to prevent doping use and develop a monitoring tool for doping prevention. The method used in this research was DESIGN-Based Research (DBR), covering the analysis, design, development, and reflection stages. The data sources involved in this research were administrators, medical officers, coaches, and disabled athletes from the NPCI (National Paralympic Committee Indonesia) Central Java Province. Data collection techniques employed were questionnaires and semi-structured interviews. The reflection stage included the validation or assessment of the product by doping experts, medical professionals, and media experts. The data obtained from this research and development were both qualitative and quantitative. Experts in the field used Aiken's V coefficient to test the validity. The product received an Aiken V value of 0.92 from doping and medical experts and 0.82 from media experts in the expert validation results. This value indicated that the experts considered the product highly valid. With the development, this product is expected to fulfill the needs of doping prevention efforts. Further research is needed to assess the effectiveness of this product in preventing the use of doping among athletes with disabilities.